The Repatriation Campaigns of People’s Democracies 1954–1956 - Cseresnyés, Ferenc (Acta Scientiarum Socialium, 2015)
The Repatriation Campaigns of People’s Democracies 1954–1956 During the Cold War the intention to gain political influence over migrant groups (and to entice them to come home), or to retain it (and to successfully integrate them into society) was part of the foreign-policy struggle between the two opposing power blocks. The Post-Stalin Soviet foreign policy has thrown itself into this political struggle with a remarkably flexible institutional and political-ideological aim. The Eastern European small and medium allies have followed the example of „the big brother” within their own capacities. The Hungarian foreign policy was particularly adept in this at the time whose technics of temptation to lure migrants home from abroad formed the basis of the similar or renewed effort of the Kádár government from the end of 1956 onward.
Keywords: Displaced Persons (DPs); stateless persons; refugees; emigrants – emigration; repatriation; United Nations High Commissioner for Refugees; repatriation propaganda; camp psychosis; forced repatriation; double agent; World Federation of Hungarians; political selection of would-be repatriates